2013
DOI: 10.1200/jco.2012.45.6400
|View full text |Cite
|
Sign up to set email alerts
|

90Yttrium-Ibritumomab Tiuxetan Consolidation of First Remission in Advanced-Stage Follicular Non-Hodgkin Lymphoma: Updated Results After a Median Follow-Up of 7.3 Years From the International, Randomized, Phase III First-Line Indolent Trial

Abstract: (90)Y-ibritumomab consolidation after achieving PR or CR/CRu to induction confers 3-year benefit in median PFS with durable 19% PFS advantage at 8 years and improves TTNT by 5.1 years for patients with advanced FL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
114
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 17 publications
4
114
1
2
Order By: Relevance
“…An initial randomized clinical trial with patients with relapsed FL, including transformed lymphoma, showed response rates of 80% in the 90 YIT group and 56% in the rituximab group; the complete response (CR) rates were 30% and 16%, respectively (Witzig et al, 2002). The second type of radiotherapy, YIT as consolidation therapy after various frontline chemotherapies for FL was shown to increase the PFS rate at 8 years from 32% to 48% (Morschhauser et al, 2013).Although the benefits of 90 YIT as treatment for advancedstage FL in the frontline and relapse settings are well documented, little data exist that document whether individuals with early-stage low-grade B-cell lymphomas benefit from 90 YIT therapy. …”
mentioning
confidence: 99%
“…An initial randomized clinical trial with patients with relapsed FL, including transformed lymphoma, showed response rates of 80% in the 90 YIT group and 56% in the rituximab group; the complete response (CR) rates were 30% and 16%, respectively (Witzig et al, 2002). The second type of radiotherapy, YIT as consolidation therapy after various frontline chemotherapies for FL was shown to increase the PFS rate at 8 years from 32% to 48% (Morschhauser et al, 2013).Although the benefits of 90 YIT as treatment for advancedstage FL in the frontline and relapse settings are well documented, little data exist that document whether individuals with early-stage low-grade B-cell lymphomas benefit from 90 YIT therapy. …”
mentioning
confidence: 99%
“…OS or PFS were both 67% at 7.5 years, with 3 patients dying while still in CR. While the majority of chemotherapy-RIT consolidation studies reporting excellent outcomes have been conducted in previously untreated patients [21], in our study there was notably no significant difference in the ORR, PFS, or OS of patients that had received one versus more than one prior regimen, and this protocol also effectively salvaged patients with progressive disease to prior therapies. In two reports, data from the four registration trials of Zevalin were analyzed retrospectively.…”
Section: Discussionmentioning
confidence: 44%
“…This compares favorably with the data reported previously with ibritumomab tiuxetan, albeit in larger patient cohorts. 13,14 Only 1 of 6 patients relapsed in the radiation field, with the infield-only relapse rate of 16% to 18% remaining extremely consistent across prior SWOG, Eastern Cooperative Oncology Group (ECOG), and British Columbia Cancer Agency studies. This contrasts with 28% to 34% relapse rate seen in Groupe d'Etude des Lymphomes de l'Adulte (GELA) studies, where a number of patients did not receive radiation as prescribed, and the radiation was given later on average.…”
Section: Discussionmentioning
confidence: 59%